Allogeneic adipose tissue-derived mesenchymal stem cells in ischaemic stroke (AMASCIS-02): a phase IIb, multicentre, double-blind, placebo-controlled clinical trial protocol. Issue 8 (9th August 2021) - de Celis-Ruiz, Elena; Fuentes, Blanca; Moniche, Francisco; Montaner, Joan; Borobia, Alberto M; Gutiérrez-Fernández, Maria; Díez-Tejedor, Exuperio
Abstract : Introduction: Stroke is a serious public health problem, given it is a major cause of disability worldwide despite the spread of recanalisation therapies. Enhancement of brain plasticity with stem cell administration is a promising innovative therapy to reduce sequelae in these patients. Methods and analysis: We have developed a phase IIb, multicentre, randomised, double-blind, placebo-controlled clinical trial protocol to evaluate the safety and efficacy of intravenous administration of allogeneic adipose tissue-derived mesenchymal stem cells (AD-MSCs) in patients with acute ischaemic stroke, concurrently with conventional stroke treatment. Thirty patients will be randomised on a 1:1 basis to receive either intravenous placebo or allogeneic AD-MSCs as soon as possible within the first 4 days from stroke symptom onset. Patients will be followed up to 24 months after randomisation. The primary objective is the safety assessment of early intravenous administration of allogeneic AD-MSCs by reporting all adverse events and neurological or systemic complications in both treatment groups. Secondary objectives assess efficacy of early intravenous AD-MSC treatment in acute ischaemic stroke by evaluating changes in the modified Rankin Scale and the National Institutes of Health Stroke Scale throughout the follow-up period. In addition, brain repair biomarkers will be measured at various visits. Ethics and dissemination: This clinical trial has been approved by the Clinical Research Ethics Committee of La Paz University Hospital (Madrid, Spain) and by the Spanish Agency of Medication and Health Products and has been registered in Eudra CT (2019-001724-35) and ClinicalTrials.gov (NCT04280003 ). Study results will be disseminated through peer-reviewed publications in Open Access format and at conference presentations.